Предмет: Математика,
автор: DenisGraf
Упростить выражения :
1) (c+2)(c-3)-(c-1)^2
2)(x-3)(x+3)+x(2-x)
3)(y-x)^2-x(x-2y)
Очень срочно , заранее спасибо
Ответы
Автор ответа:
0
1) (c+2)*(c-3)-(c-1)^2 = с² - 3с + 2с - 6 - с² + 2с - 1 = с² - с² - 3с + 2с + 2с - 6 -1=с - 7
2) (x-3)*(x+3)+x*(2-x) = х² + 3х - 3х - 9 + 2х - х² = х² - х² + 3х - 3х + 2х - 9 = 2х - 9
3) (y-x)^2-x*(x-2y) = у² - 2ху + х² - х² + 2ху = у²
2) (x-3)*(x+3)+x*(2-x) = х² + 3х - 3х - 9 + 2х - х² = х² - х² + 3х - 3х + 2х - 9 = 2х - 9
3) (y-x)^2-x*(x-2y) = у² - 2ху + х² - х² + 2ху = у²
Похожие вопросы
Предмет: Математика,
автор: jlexsg
Предмет: Математика,
автор: DHCP
Предмет: География,
автор: vdjwuev1838
Предмет: Математика,
автор: gaflan0912r
Предмет: Математика,
автор: LIKSEN